Seismic Inversion as An Exciting Tool to Delineate Facies Distribution in Tiaka Carbonate Reservoirs, Sulawesi -Indonesia - , D. Hasanusi ([Yogyakarta] : Departemnts of Geological Engineering Faculty of E, 2009)
After the drilling of six wells that successfully found oil, an unexpected dry well was encountered in the Tiaka field, Tomori block, Sulawesi - Indonesia. The Tiaka field has carbonate reservoirs that produce oil from its deeper Early Miocene Tomori limestone as the primary objective, while limited gas-bearing zones can be found in the shallower Minahaki limestone. The dry well was a surprise as a previous study indicated that this was a favorable location to drill. In order to reduce the risk for the future drilling plan, and to get a better understanding of the lateral facies distribution of reservoirs in the field, a constrained sparse spike inversion was applied to convert the 2D full-stack seismic data recorded in the area into 2D acoustic impedance lines, calibrated to the existing wells. The dry well, however, was treated as a blind well to validate the inversion result. The inversion and interpretation of the seismic data itself has some challenges to be resolved. First, the seismic lines consist of six vintages that were recorded using different sources, resulting in variations in signal-to-noise ratio, frequency content, and seismic amplitude dynamic range. Second, the field has a strong dips (18-25 degrees) that affect the structural interpretation from survey lines at different orientations. Third, and most importantly, there is strong overlap in the acoustic impedance domain between shale and the targeted porous limestone. This paper will discuss how tho!ieissues were resolved, or at least reduced. The inversion result confirmed that the dry well was drilled in a tight limestone area, while oil wells were drilled in a porous limestone area. As a result of this study, three wells are planned to be drilled, with one well recently completed. This well encountered a significant oil-bearing zone in the Tomori porous limestone as predicted by the inversion.